Keterkaitan Pasar Valuta Asing dan Saham di Indonesia dengan Beberapa Negara Mitra Utama: 1998-2009 - Soelistianingsih, Lana (Jurnal Ekonomi dan Pembangunan Indonesia, 2010)
Using co-integration, the results show that the movement of Indonesian foreign exchange market and capital market has moved to long-run equilibrium with other currencies and indices from partner countries, while the short-run equilibrium between markets have been proved by using VECM. The Indonesian case supports portfolio balance approach introduced by Frankel. The increasing of IHSG attracts capital inflows and makes the demand for domestic currency higher, and IDR becomes appreciation. Indonesian market has strong linkages with Asian regional markets especially with Hong Kong market, while having no relationship with US market.